2020
DOI: 10.1001/jamaneurol.2019.4656
|View full text |Cite|
|
Sign up to set email alerts
|

Assessment of the Validity of the 2HELPS2B Score for Inpatient Seizure Risk Prediction

Abstract: IMPORTANCESeizure risk stratification is needed to boost inpatient seizure detection and to improve continuous electroencephalogram (cEEG) cost-effectiveness. 2HELPS2B can address this need but requires validation. OBJECTIVE To use an independent cohort to validate the 2HELPS2B score and develop a practical guide for its use. DESIGN, SETTING, AND PARTICIPANTSThis multicenter retrospective medical record review analyzed clinical and EEG data from patients 18 years or older with a clinical indication for cEEG an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
82
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(86 citation statements)
references
References 37 publications
3
82
1
Order By: Relevance
“…The cohort study of 2111 participants with continuous EEG showed that any highly epileptiform discharges during the first hour of EEG (i.e. a 2HELPS2B score of ≥2) indicated that at least 24 h of recording was recommended to detect seizures ( Struck et al , 2020 ). In 121 critically ill children, the first non-convulsive seizures were all captured within 24 h in 28 non-convulsive seizures ( McCoy et al , 2011 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The cohort study of 2111 participants with continuous EEG showed that any highly epileptiform discharges during the first hour of EEG (i.e. a 2HELPS2B score of ≥2) indicated that at least 24 h of recording was recommended to detect seizures ( Struck et al , 2020 ). In 121 critically ill children, the first non-convulsive seizures were all captured within 24 h in 28 non-convulsive seizures ( McCoy et al , 2011 ).…”
Section: Discussionmentioning
confidence: 99%
“…Lateralized PDs regardless of frequencies and lateralized RDA with high frequencies are associated with seizures ( Rodriguez Ruiz et al ., 2017 ). Brief potentially ictal rhythmic discharges may indicate ictal–interictal continuum for consideration of the treatment of seizures ( Yoo et al , 2014 ; Struck et al , 2020 ). One of the ictal EEG criteria must persist for longer than 10 s under the Salzburg criteria ( Leitinger et al , 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Our results confirm that SE is common in patients in neurocritical care, but the prevalence of seizure activity in this study is even higher than previously reported. A review of the literature on cEEG and detection of status epilepticus and seizures in adults published in the past 5 years are provided in Table 3 14,17–40 . 51–59 Most studies on seizures activity and cEEG performed in neurocritically ill patients are from the United States.…”
Section: Discussionmentioning
confidence: 99%
“…Recent advances have enabled a better understanding of the global epidemiology of this entity [ 2 , 3 , 4 ]. The greater implementation of continuous EEG monitoring has certainly contributed to this [ 5 , 6 ].…”
mentioning
confidence: 99%